2011
DOI: 10.2174/1874285801105010072
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a Human Diarrheagenic Escherichia coli Clone in Captivity Kept Psittacidaes

Abstract: Bacterial cultures of cloaca swabs from 86 captivity kept psittacidaes revealed 17 Escherichia coli bearing birds sharing strains which, on the basis of enterobacterial repetitive intergenic consensus (ERIC) PCR analysis, proved to be genetically similar. Further, triplex PCR specific for the genetic markers chuA, yjaA, and TSPE4.C2 was used to assign the strains to the E. coli reference collection (EcoR) B2 group. One strain of each, from the enteropathogenic (EPEC), enteroaggregative (EAEC) and Shiga toxin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
(23 reference statements)
0
6
0
2
Order By: Relevance
“…coli (EPEC) pathotypes 7,8,9 . However, the diversity of 18.6% in blue-fronted parrots (Amazona aestiva) 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…coli (EPEC) pathotypes 7,8,9 . However, the diversity of 18.6% in blue-fronted parrots (Amazona aestiva) 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Such bacteria are considered abnormal inhabitants of psittacine birds, so they are viewed by some as pathogenic and opportunistic microorganisms in this context 5,6,7 . However, there is controversy about the meaning of the infection in clinically healthy birds, such as whether they are a reservoir of potentially pathogenic bacterial species for other birds and mammals 7,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Adicionalmente, Marietto-Gonçalves et al (2011) constataram a presença de cepas de E. coli EPEC, EAEC e STEC em pelo menos um isolado de psitacídeo, demostrando mais uma vez que essas aves podem ser reservatórios de cepas com potencial zoonótico. Outros patotipos de E. coli vêm sendo paulatinamente isolados em psitacídeos, como exemplificados por estudo realizado por Knöbl et al (2011).…”
Section: Escherichia Coliunclassified
“…Putative EAEC have been isolated from diarrhoeic dogs in Germany (Breitwieser, 1999). No EAEC strains were found in a study of 24 sick Brazilian parrots (Knoebl et al, 2011), but one EAEC strain was identified from bacterial cultures of cloacal swabs from 86 captive kept psittacine birds in Brazil (Marietto-Goncalves et al, 2011). EAEC have been isolated from dogs and cats and at low levels from poultry manure in Brazil (Puno-Sarmiento et al, 2013;Puno-Sarmiento et al, 2014).…”
Section: Public Health Significance Of Eaec Related To the Handling mentioning
confidence: 99%